Sejarah Bangsa Israel Awal dalam Perspektif Tafsir Sejarah Teologi Alkitabiah dan Arkeologi Biblikal - Adiwidjajanto, Koes (Program Studi Studi Agama-Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2016)
This article is about history of ancient Israel in biblical era and how the sacred scripture introduces information of the ancient people. We have to know how to read the scriptures. They demand an imaginative effort, as Karen Armstrong said, that can sometimes be as perplexing and painful job. The true meaning of scriptures can never be wholly comprised in a literal reading of the text, since that text points beyond itself to reality that cannot be totally grasp. Our academic world cultivates us to look for the words between the lines. We expect a text to express its idea as clearly as possible. In a philosophical or historical work, we will often judge writers by the precision and consistency of their arguments. There are Jews and Christians who have come to apply the same standards to Bible. Some, for example, have argued that the chapters of Genesis and Chronicles are factual accounts on history of ancient Israel people. But what we need to the Bible does not present its truths to us in this way. This article presents two main methods to understand the historical contains of the biblical text: historical interpretation and biblical archaeology to know at some profound level the sacred history of biblical Israelites people